Analysis of the Cost Effectiveness of Retrofitting Using the Benefit-Cost Ratio and the Breakeven Point Analysis - Banjara, Sarbesh; Shrestha, Sanam (Journal of UTEC Engineering Management, 2025)
The retrofitting of buildings has become an important strategy for improving seismic resilience in Nepal after the Gorkha earthquake. The National Reconstruction Authority (NRA) led the effort to rebuild earthquake-damaged infrastructure and included retrofitting as a keyway to strengthen weak structures. This study looks at the economic feasibility of retrofitting low-strength masonry buildings by examining the breakeven period and benefit-cost ratio (BCR) in different cost-benefit scenarios for the building that has been retrofitted post-Gorkha earthquake with the assistance of the NRA. Data were gathered through surveys with stakeholders, including homeowners, engineers, and officials, and verified using government cost norms and district unit rates. Benefit estimates came from existing literature and were analyzed using financial metrics like Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Breakeven Point (BEP). The results show that the breakeven period for retrofitting is 7.26 years, which fits well within the usual planning timeframe. Additionally, the benefit-cost ratio stays above one, even when retrofitting costs rise by 20% and expected benefits drop by 20%. These findings highlight the cost-effectiveness and financial sustainability of retrofitting to reduce seismic risks. This study offers useful insights for policymakers, engineers, and stakeholders who want to improve the resilience of Nepal’s built environment through targeted retrofitting efforts.